Preparation method of Cu2O microsphere structure yarn dyed fabric
The disordered structural color layer was prepared through the two-step liquid phase reduction method and spraying method of Cu2O microspheres, which solved the problem of fabric dyeing easy fading and environmental pollution, and achieved a bright, antibacterial and environmentally friendly structural color fabric, which improved the practicality of the fabric and productivity.
Patent Information
- Application Number
- CN202411378179.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The existing fabric dyeing technology has problems such as dyes that are prone to fading, environmental pollution, complex processes and high energy consumption, and structural coloring is low in feasibility and insufficient practicality on flexible substrates.
Cu2O microspheres were used to synthesize monodispersed single crystal spheres through two-step liquid phase reduction method, and spraying method to prepare disordered structural color layers on the fabric to form a bright and non-fading structured fabric.
It achieves bright and non-fading color output, reduces production costs and energy consumption, has good antibacterial properties, and is in line with the concept of green and environmental protection development.
Smart Images

Figure CN119265955A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of textile ecological coloring, and particularly relates to a method for preparing a Cu2O microsphere structural color fabric. Background Art
[0002] The main way to color fabrics is to attach colored natural or synthetic dyes to fabric fibers to produce colors, relying on the chemical chromophores in the colored dyes to absorb light of specific wavelengths, so that the human eye can produce color perception. This type of color belongs to pigment color. However, in the context of advocating green and sustainable development, there are some problems: dyes and various chemicals and auxiliaries need to be added during the dyeing process, the processing technology is cumbersome and complicated, energy consumption is high, and water consumption is high; a large amount of difficult-to-treat colored wastewater will be generated during the production process, the treatment cost is high, and it is easy to pollute the environment. In response to the above problems, new technologies such as reactive dye salt-free dyeing technology, foam dyeing and finishing technology, and supercritical carbon dioxide dyeing technology have been proposed to try to solve this problem. However, the structure of the pigment molecule itself is complex and there are several aromatic rings, so it is difficult to synthesize it artificially. In addition, the structure of the pigment molecule itself is unstable and it is easy to decompose under long-term sunlight, which affects the normal use of the fabric.
[0003] Compared with conventional fabric dyeing technology, structural color generation has the advantages of being eco-friendly, colorful, and anti-fading. In the context of advocating green and sustainable development, it has outstanding advantages and has attracted widespread attention from scientific researchers. However, this type of technology still has the following problems: (1) Photonic crystal structures generate colors through photonic band gaps, which requires highly ordered three-dimensional structures, which reduces the feasibility of their construction on flexible substrates with uneven surfaces. At the same time, the iridescent effect of structural colors also greatly reduces the practicality of fabrics. (2) Fabrics with structural colors rely on structural color layers to generate colors. Once the structural color layer falls off, the color will disappear. Therefore, the fastness of the structural color layer is the key to determining the practical application of structural colors in fabrics. Limited by the color generation mechanism and multi-layer structure of structural colors, it is still a challenge to achieve bright, non-iridescent, and high color fastness color output on fabrics. The use of uniform microspheres or polyhedrons with high refractive index to prepare amorphous fabrics with structural colors is expected to solve the above problems. Cuprous oxide (Cu2O) is a commonly used semiconductor material with a high refractive index and electromagnetic resonance properties similar to those of precious metals. The electromagnetic field distribution of its electromagnetic resonance changes with the change of the medium. It is an ideal material for constructing brightly colored short-range ordered and long-range disordered structures and realizing double-sided asymmetric structural colors. Summary of the invention
[0004] The technical problem to be solved by the invention is to provide a method for preparing a Cu2O microsphere structure color fabric which is bright in color and not easy to fade.
[0005] In order to solve the above technical problems, the present invention provides a method for preparing a Cu2O microsphere structured colored fabric, comprising the following steps:
[0006] 1) Prepare copper source precursor solution:
[0007] Polyvinyl pyrrolidone (PVP), trisodium citrate dihydrate (NaCit·2H2O) and dibasic copper salt are added to a mixed solvent consisting of diol and deionized water in a molar ratio of 7.8:0.8-1.2:1-1.8, and dispersed uniformly (by stirring and ultrasonic dispersion) to form a copper source precursor solution (a clear and transparent light blue solution);
[0008] 2) Prepare sodium hydroxide solution:
[0009] Dissolve sodium hydroxide (NaOH) in ionized water to obtain a sodium hydroxide solution (sodium hydroxide aqueous solution);
[0010] 3) Prepare reducing agent solution:
[0011] dissolving a reducing agent in deionized water to obtain a reducing agent solution;
[0012] 4) Under vigorous stirring conditions, the sodium hydroxide solution prepared in step 2) is added (dropped) to the copper source precursor solution prepared in step 1) according to a molar ratio of sodium hydroxide: binary copper salt = 3 to 6:1, and after vigorous stirring, a solution 1 (a dark blue clear solution) is obtained;
[0013] 5) Under stirring conditions, according to the molar ratio of reducing agent: binary copper salt = 1.05-1.2:1, the reducing agent solution obtained in step 3) is added (dropped) to the solution 1 obtained in step 4), and dispersed evenly (stirred, ultrasonically dispersed evenly) to obtain solution 2 (during the stirring process, the dark blue clear solution turns into a turbid solution with other colors, that is, the obtained is an emulsion containing cuprous oxide microspheres);
[0014] 6) performing solid-liquid separation on the solution 2 obtained in step 5), washing and drying the separated solid to obtain Cu2O single crystal spheres;
[0015] 7) Prepare Cu2O single crystal sphere dispersion:
[0016] Cu2O single crystal spheres are dispersed in anhydrous ethanol to obtain a uniformly dispersed Cu2O single crystal sphere dispersion;
[0017] In the Cu2O single crystal sphere dispersion liquid, the concentration of the Cu2O single crystal sphere dispersion is 1.% to 2.5wt% (preferably 2wt%);
[0018] 8) Preparation of binder dispersion:
[0019] The binder is dispersed in deionized water to obtain a uniformly dispersed binder dispersion;
[0020] In the binder dispersion, the concentration of the binder dispersion is 5% to 30wt% (preferably 20wt%);
[0021] 9) Firstly, the adhesive dispersion is sprayed on the surface of the fabric, and then the fabric is dried for the first time to obtain the pretreated fabric;
[0022] Then, a Cu2O single crystal ball dispersion is sprayed on the surface of the pretreated fabric, and then secondary drying is performed to obtain a Cu2O microsphere structural color fabric (a structural color photonic crystal fabric).
[0023] As an improvement of the preparation method of the Cu2O microsphere structure colored fabric of the present invention:
[0024] In step 1), the binary copper salt is any one of the following: copper acetate monohydrate, copper nitrate trihydrate, copper sulfate, copper chloride;
[0025] In step 3), the reducing agent is any one of the following: ascorbic acid, hydroxylamine hydrochloride;
[0026] The binder in step 8) is a resin binder.
[0027] As a further improvement of the preparation method of the Cu2O microsphere structure colored fabric of the present invention:
[0028] In step 1), the diol is any one of the following: butanediol, pentanediol, ethylene glycol, hexanediol, and diethylene glycol.
[0029] In step 8), the resin binder is any one of the following: polyacrylate (PA), polyvinyl alcohol (PVA).
[0030] As a further improvement of the preparation method of the Cu2O microsphere structure colored fabric of the present invention:
[0031] In the step 1), the ratio of the dibasic copper salt to the mixed solvent is 0.0017 mol to 0.0051 mol / 130 ml to 260 ml; in the mixed solvent, the volume ratio of diol to deionized water is 2 to 4:10 (preferably 3:10);
[0032] In the step 2), the concentration of the sodium hydroxide solution is 0.3 to 1.0 M;
[0033] In the step 3), the concentration of the reducing agent solution is 0.1M to 1.0M.
[0034] As a further improvement of the preparation method of the Cu2O microsphere structure colored fabric of the present invention:
[0035] Steps 1) to 8) can be performed at a temperature of 5 to 50° C. (e.g., room temperature of 10 to 25° C.);
[0036] The rate of vigorous stirring in step 4) is 1000-1200 r / min, and the stirring rate in the remaining steps is 300-900 r / min;
[0037] In the step 1), the stirring time is 20 min to 3 h; the ultrasonic dispersion time is 5 to 60 min (ultrasonic power is 100%);
[0038] In step 4), the sodium hydroxide aqueous solution is added to the copper source precursor solution by dropwise addition for 10 to 20 minutes; the vigorous stirring time is 5 to 60 minutes;
[0039] In step 5), the reducing agent solution is added to solution 1 by dripping twice, and the dripping time of each time is 18 to 38 seconds; the interval time between two dripping is 5 to 30 minutes; after the dripping is completed, it is stirred for 60 to 80 minutes and ultrasonically dispersed for 5 to 60 minutes;
[0040] Note: Keep stirring during the interval between two drops;
[0041] In step 6), a centrifuge is used to separate solid and liquid, and the centrifugation is performed at a speed of 4000 to 12000 r / min for 5 to 30 min;
[0042] The stirring time of step 7) is 5 to 30 minutes;
[0043] The stirring time of step 8) is 5 to 30 minutes.
[0044] As a further improvement of the preparation method of the Cu2O microsphere structure colored fabric of the present invention:
[0045] The step 9) is: spraying (spraying binder dispersion / spraying Cu2O single crystal sphere dispersion) is performed by a spray gun connected to an air compressor, the pressure applied by the air compressor is 0.5PSI, and the diameter of the spray gun is 0.2mm.
[0046] As a further improvement of the preparation method of the Cu2O microsphere structure colored fabric of the present invention:
[0047] In the step 6), washing is performed using a mixed solution of water and ethanol; in the mixed solution, the volume ratio of water to ethanol is 1:1; and drying is performed in a vacuum oven at 50±10°C for 3±0.5h;
[0048] In the step 9), the first drying is to place the product in a 100±10°C air drying oven for 1±0.1 min; the second drying is to place the product in a blast drying oven for 3±0.3 min at 160±10°C.
[0049] Compared with the prior art, the present invention has the following technical advantages:
[0050] The invention discloses a method for preparing a structural color photonic crystal fabric. The method comprises the following steps: synthesizing monodisperse Cu2O single crystal balls by a two-step liquid phase reduction method, preparing cuprous oxide microspheres by strictly controlling the reaction ratio of trisodium citrate dihydrate (NaCit·2H2O) and dibasic copper salt (molar ratio 0.8-1.2:1), and obtaining microspheres with a particle size of 165nm-275nm; and then preparing a disordered structural color layer of Cu2O single crystal balls on the fabric by a spraying method to obtain a fabric with structural color. The structural color fabric has bright color and is not easy to fade, which solves the disadvantage that chemical organic dyes are easy to fade and harmful to human body. At the same time, since the copper oxide and cuprous oxide (Cu2O) nanoparticles can interact with the cell membrane of bacteria or fungi to destroy their cell structure and function, thereby inhibiting their growth and reproduction. It is detected that the structural color fabric has good antibacterial property against Staphylococcus aureus and Escherichia coli. The antibacterial mechanism is that the nanoparticles have strong antibacterial activity against a variety of pathogenic microorganisms, so the prepared structural color fabric has good antibacterial property. The whole production process is easy to operate, with little energy and water consumption, low production cost, in line with the development concept of green environmental protection, and has a high practical application prospect. The whole production process is easy to operate, with little energy and water consumption, low production cost, in line with the development concept of green environmental protection, and has a high practical application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings.
[0052] Figure 1 SEM image of Cu2O microspheres with a particle size of 165±10nm;
[0053] Figure 2 3D video microscopy image of Cu2O microspheres with a particle size of 165±10nm;
[0054] Figure 3 SEM image of Cu2O microspheres with a particle size of 245±10nm;
[0055] Figure 4 3D video microscopy image of Cu2O microspheres with a particle size of 245±10nm.
[0056] Figure 5 These are photos of composite structured color fabrics before and after washing. DETAILED DESCRIPTION
[0057] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0058] The following steps 1) to 8) can be performed at a temperature of 5 to 50° C., for example, at room temperature of 25° C.;
[0059] The vigorous stirring rate of step 4) is 1100-1200 r / min;
[0060] The stirring rate of the remaining steps is 600-800 r / min.
[0061] All stirring was magnetic.
[0062] Embodiment 1: A method for preparing a Cu2O microsphere structure color fabric, comprising the following steps:
[0063] 1) Prepare copper source precursor solution
[0064] 1.4969 g (0.01326 mol) of polyvinyl pyrrolidone (PVP), 0.50 g (0.0017 mol) of trisodium citrate dihydrate (Na3C6H5O7·2H2O) and 0.33426 g (0.0017 mol) of copper acetate monohydrate (C4H3CuO4·H2O) were mixed in a system consisting of 30 mL of ethylene glycol and 100 mL of deionized water, and magnetically stirred for 20 min and ultrasonically vibrated for 10 min to disperse uniformly to form a clear and transparent light blue solution, which is a copper source precursor solution;
[0065] That is, the molar ratio of PVP:NaCit·2H2O:C4H3CuO4·H2O=7.8:1:1.
[0066] 2) Prepare sodium hydroxide solution
[0067] Dissolve 0.01 mol of sodium hydroxide (NaOH) in 20 mL of deionized water to obtain a 0.5 M sodium hydroxide solution;
[0068] 3) Prepare ascorbic acid solution
[0069] Dissolve 0.0018 mol of ascorbic acid (C6H8O6) in 15 mL of deionized water to obtain a 0.12 M ascorbic acid solution;
[0070] 4) Under the condition of vigorous magnetic stirring, the sodium hydroxide solution prepared in step 2) was added dropwise to the copper source precursor solution prepared in step 1) at a dropping rate of 2 mL / min (i.e., the dropping time was about 10 minutes). After the addition was completed, the vigorous magnetic stirring was continued for 10 minutes to form a dark blue clear solution, which was named Solution 1.
[0071] 5) Under magnetic stirring, the ascorbic acid solution prepared in step 3) was added to the solution 1 prepared in step 4) at a drop rate of 0.4 mL / s in two equal portions (i.e., each addition time of the ascorbic acid aqueous solution was about 18.75 s), and the time interval between the two additions of the ascorbic acid aqueous solution was 5 min (stirring was still maintained during this 5 min interval);
[0072] After all the ascorbic acid solution was added, the solution was stirred magnetically for 60 min and ultrasonically shaken for 10 min. At this time, it was found that the solution 1 changed from a dark blue clear solution to a turbid solution with other colors. The solution was named solution 2 (an emulsion containing cuprous oxide microspheres).
[0073] 6) Place the solution 2 prepared in step 5) into a centrifuge and centrifuge at 8000 r / min for 10 min. Wash the solid obtained by centrifugation twice with a mixed solution of water and ethanol (water: ethanol = 1:1 volume ratio), and then dry it in a vacuum oven at 50° C. for 3 h to obtain Cu2O single crystal spheres (particle size is about 210±10 nm);
[0074] 7) Preparation of Cu2O single crystal sphere dispersion
[0075] The synthesized Cu2O single crystal spheres were dispersed in anhydrous ethanol and stirred for 20 minutes to obtain a uniformly dispersed Cu2O single crystal sphere dispersion liquid, wherein the concentration of the Cu2O single crystal spheres in the dispersion liquid was 2 wt%.
[0076] 8) Preparation of PA binder dispersion:
[0077] The PA binder, polyacrylate (PA), was dispersed in deionized water and stirred for 30 minutes to obtain a uniformly dispersed binder dispersion (milky white solution). The concentration of polyacrylate (PA) in the binder dispersion was 20wt%.
[0078] 9) Preparation of structural color fabrics
[0079] According to each cm 2 The fabric is matched with 1 mg of the binder dispersion in an amount ratio, and the binder dispersion obtained in step 8) is sprayed on the surface of the fabric (black polyester fabric) by a spray gun connected to an air compressor, and then placed in a 100° C. air drying oven for 1 min to obtain a pretreated fabric;
[0080] According to each cm 2 The surface of the fabric is prepared with 15 μL of Cu2O single crystal sphere dispersion, and the Cu2O single crystal sphere dispersion is sprayed on the surface of the fabric pretreated with PA using the same method (through a spray gun connected to an air compressor), and then placed in a forced air drying oven at 160°C for 3 minutes to obtain a structural color photonic crystal fabric with yellow color.
[0081] Note: Set the compressor pressure to 0.5PSI and the spray gun diameter to 0.2mm.
[0082] Example 2-1: Step 1) in Example 1 is modified as follows: the dosage ratio of "polyvinyl pyrrolidone, trisodium citrate dihydrate and copper acetate monohydrate" is changed to "1.4969 g (0.01326 mol) of polyvinyl pyrrolidone (PVP), 0.40 g (0.00136 mol) of trisodium citrate dihydrate (Na3C6H5O7·2H2O) and 0.33426 g (0.0017 mol) of copper acetate monohydrate (C4H3CuO4·H2O)"; that is, the molar ratio of PVP:NaCit·2H2O:C4H3CuO4·H2O=7.8:0.8:1 is set. The rest is the same as Example 1. A blue structural color photonic crystal fabric is obtained.
[0083] Example 2-2: Step 1) in Example 1 is modified as follows: the dosage ratio of "polyvinyl pyrrolidone, trisodium citrate dihydrate and copper acetate monohydrate" is changed to "1.4969 g (0.01326 mol) of polyvinyl pyrrolidone (PVP), 0.45 g (0.00153 mol) of trisodium citrate dihydrate (Na3C6H5O7·2H2O) and 0.33426 g (0.0017 mol) of copper acetate monohydrate (C4H3CuO4·H2O)"; that is, the molar ratio of PVP:NaCit·2H2O:C4H3CuO4·H2O=7.8:0.9:1 is set. The rest is the same as Example 1. A green structural color photonic crystal fabric is obtained.
[0084] Example 2-3: Step 1) in Example 1 is modified as follows: the dosage ratio of "polyvinyl pyrrolidone, trisodium citrate dihydrate and copper acetate monohydrate" is changed to "1.4969 g (0.01326 mol) of polyvinyl pyrrolidone (PVP), 0.55 g (0.00187 mol) of trisodium citrate dihydrate (Na3C6H5O7·2H2O) and 0.33426 g (0.0017 mol) of copper acetate monohydrate (C4H3CuO4·H2O)"; that is, the molar ratio of PVP:NaCit·2H2O:C4H3CuO4·H2O=7.8:1.1:1 is set. The rest is the same as Example 1. A structural color photonic crystal fabric with orange color is obtained.
[0085] Example 2-4: Step 1) in Example 1 is modified as follows: the dosage ratio of "polyvinyl pyrrolidone, trisodium citrate dihydrate and copper acetate monohydrate" is changed to "1.4969 g (0.01326 mol) of polyvinyl pyrrolidone (PVP), 0.60 g (0.00204 mol) of trisodium citrate dihydrate (Na3C6H5O7·2H2O) and 0.33426 g (0.0017 mol) of copper acetate monohydrate (C4H3CuO4·H2O)"; that is, the molar ratio of PVP:NaCit·2H2O:C4H3CuO4·H2O=7.8:1.2:1 is set. The rest is the same as Example 1. A structural color photonic crystal fabric with red color is obtained.
[0086] The comparison of the particle size and color of the Cu2O single crystal spheres obtained in the above Examples 2-1 to 2-4 and the Cu2O single crystal spheres obtained in Example 1 is shown in Table 1 below.
[0087] Table 1. Particle size and color of Cu2O single crystal spheres obtained in each case
[0088]
[0089]
[0090] According to the comparison in Table 1, it can be seen that by changing the dosage of NaCit, Cu2O microspheres with different particle sizes can be obtained, and the colors of the microspheres are also different.
[0091] The SEM image corresponding to Example 2-1 is as follows Figure 1 As shown; the three-dimensional video microscope image corresponding to Example 2-1 is as shown Figure 2 As shown;
[0092] The SEM images corresponding to Examples 2-3 are as follows Figure 3 As shown; the three-dimensional video microscope image corresponding to Example 2-3 is as shown Figure 4Example 3: A method for preparing a Cu2O microsphere structure color fabric, comprising the following steps:
[0093] 1) Prepare copper source precursor solution
[0094] 0.02652 mol of polyvinyl pyrrolidone (PVP), 0.0034 mol of trisodium citrate dihydrate (NaCit·2H2O) and 0.0051 mol of copper acetate monohydrate (C4H3CuO4·H2O) were mixed in a system consisting of 60 mL of ethylene glycol and 200 mL of deionized water, magnetically stirred for 3 h, and ultrasonically vibrated for 10 min, so as to be evenly dispersed to form a clear and transparent light blue solution; this is a copper source precursor solution;
[0095] That is, the molar ratio of PVP:NaCit·2H2O:C4H3CuO4·H2O=7.8:1:1.5.
[0096] Step 2) to step 7) are equivalent to step 2) to step 7) of embodiment 1;
[0097] 8) Prepare adhesive
[0098] 0.30g carbon black powder and 49.7mL deionized water were placed in a 100mL beaker, and ultrasonically vibrated for 20min to prepare a 0.6wt% carbon black solution. Then 8mL of 0.6wt% carbon black solution, 5.00g polyacrylate (PA), 0.60g dispersing thickener (DM-5262HB Yin, Guangdong Demei Fine Chemical Group Co., Ltd.), and 20mL deionized water were placed in a beaker, and magnetically stirred for 30min to obtain a uniformly dispersed black paste adhesive.
[0099] 9) Preparation of structural color fabrics
[0100] Spread the white aramid fabric substrate on the scraper, spread the black paste adhesive on the fabric surface with a wire rod at a speed of 5 mm / s, dry it in an oven at 100°C for 1 min, repeat the scraping and drying for 3 times (the amount used each time is 1 cm 2 0.46 mg of black paste adhesive was spread on the surface of the fabric, and this process was repeated 3 times to obtain a fabric with adhesive attached to the surface.
[0101] Then, a proper amount of 2 wt% Cu2O single crystal sphere dispersion was sprayed onto the surface of the fabric treated with the binder (the amount was per cm 2 15 μL of Cu2O single crystal ball dispersion was sprayed on the surface of the fabric, and then dried in an oven at 160°C for 3 minutes to obtain a structural color photonic crystal fabric.
[0102] The present invention provides a new method for applying structural color photonic crystals on fabrics.
[0103] Embodiment 4: A method for preparing a Cu2O microsphere structure color fabric, comprising the following steps:
[0104] 1) Prepare copper source precursor solution
[0105] 0.02175 mol of polyvinyl pyrrolidone (PVP), 0.002882 mol of trisodium citrate dihydrate (NaCit·2H2O) and 0.0051 mol of copper acetate monohydrate (C4H3CuO4·H2O) were mixed in a system consisting of 60 mL of ethylene glycol and 200 mL of deionized water, and magnetically stirred for 3 h and ultrasonically vibrated for 10 min to disperse uniformly to form a clear and transparent light blue solution; this is a copper source precursor solution;
[0106] That is, the molar ratio of PVP:NaCit·2H2O:C4H3CuO4·H2O=7.8:1:1.76.
[0107] 2) Prepare sodium hydroxide aqueous solution
[0108] Dissolve 0.016 mol of sodium hydroxide (NaOH) in 40 mL of deionized water to obtain a 0.4 M sodium hydroxide solution;
[0109] 3) Prepare ascorbic acid aqueous solution
[0110] Dissolve 0.006 mol ascorbic acid in 30 mL of deionized water to obtain a 0.2 M ascorbic acid solution;
[0111] 4) Under the condition of vigorous magnetic stirring, the sodium hydroxide solution prepared in step 2) was added dropwise to the copper source precursor solution prepared in step 1) at a dropping rate of 2 mL / min (i.e., the dropping time was 20 minutes). After the dropping was completed, the vigorous magnetic stirring was continued for 10 minutes to form a dark blue clear solution; the obtained solution was named Solution 1.
[0112] 5) Under magnetic stirring, the ascorbic acid aqueous solution prepared in step 3) is added into the solution 1 prepared in step 4) at a drop rate of 0.4 mL / s in two equal portions (i.e., the ascorbic acid aqueous solution is added for about 37.5 s each time), and the time interval between the two additions of the ascorbic acid aqueous solution is 5 min (stirring is still maintained during this 5 min interval);
[0113] After all the ascorbic acid solution was added, the solution was stirred magnetically for 60 minutes and ultrasonically shaken for 10 minutes. At this time, it was found that the solution 1 changed from a dark blue clear solution to a turbid solution with other colors. The obtained solution was named solution 2 (an emulsion containing cuprous oxide microspheres).
[0114] 6) Place the solution 2 prepared in step 5) into a centrifuge and centrifuge at 8000 r / min for 10 min. Wash the solid obtained by centrifugation twice with a mixed solution of water and ethanol (water: ethanol = 1:1 volume ratio), and then dry it in a vacuum oven at 50° C. for 3 h to obtain 210±10 nm Cu2O single crystal spheres;
[0115] 7) Preparation of Cu2O single crystal sphere dispersion
[0116] Disperse 0.1g Cu2O single crystal spheres in 9.9g anhydrous ethanol and stir for 20min to obtain a 1% Cu2O single crystal sphere dispersion.
[0117] 8) Prepare PA dispersion
[0118] 5 g of polyacrylate (PA) was dissolved in 20 g of deionized water and stirred for 20 min to prepare a 20% PA dispersion;
[0119] 9) Preparation of structural color fabrics
[0120] 20% PA solution was evenly sprayed on the surface of PET fabric using a spray gun with a 0.2mm nozzle at a pressure of 20PSI (the amount was per cm 2 1 mg of PA solution was sprayed on the fabric surface) and dried at 160°C for 30 seconds. Then, 1% Cu2O single crystal sphere dispersion (dosage per cm2) was sprayed with the same spray gun. 2 15 μL of Cu2O single crystal sphere dispersion was sprayed on the fabric surface). Then the PA-Cu2O coated PET fabric was dried at 160°C for 3 min to obtain the structural color photonic crystal fabric.
[0121] The invention provides a new idea for the application of structural color photonic crystals on fabrics.
[0122] Embodiment 5, a method for preparing a Cu2O microsphere structure color fabric, comprising the following steps:
[0123] 1) Prepare copper source precursor solution
[0124] 0.02652 mol of polyvinyl pyrrolidone (PVP), 0.0034 mol of trisodium citrate dihydrate (NaCit·2H2O) and 0.0051 ml of copper acetate monohydrate (C4H3CuO4·H2O) were mixed in a system consisting of 60 mL of ethylene glycol and 200 mL of deionized water, magnetically stirred for 3 h, and ultrasonically vibrated for 10 min, so as to be evenly dispersed to form a clear and transparent light blue solution; this is a copper source precursor solution;
[0125] That is, the molar ratio of PVP:NaCit·2H2O:C4H3CuO4·H2O=7.8:1:1.5.
[0126] Step 2) to step 6) are equivalent to step 2) to step 6) of embodiment 1;
[0127] 7) Preparation of Cu2O single crystal sphere dispersion
[0128] 0.1 g of Cu2O single crystal spheres were dispersed in 9.9 g of anhydrous ethanol and stirred for 20 min to obtain a uniformly dispersed Cu2O single crystal sphere dispersion liquid. The concentration of the Cu2O single crystal spheres in the dispersion liquid was 1 wt%.
[0129] 8) Prepare PA dispersion
[0130] Dissolve 5 g of polyacrylate (PA) in 20 g of deionized water and stir for 20 min to prepare a uniformly dispersed 20% PA dispersion;
[0131] 9) Preparation of structural color fabrics
[0132] The black PET fabric was washed with ultrasonic deionized water for 15 minutes and dried in an oven.
[0133] 20% PA solution was evenly sprayed on the surface of PET fabric using a spray gun with a 0.2mm nozzle at a pressure of 20PSI (the amount was per cm 2 1 mg of PA solution was sprayed on the fabric surface) and dried at 160 ° C for 30 s. Then, 1% Cu2O single crystal nanosphere dispersion (dosage per cm) was sprayed with the same spray gun. 2 15 μL of Cu2O single crystal sphere dispersion was sprayed on the fabric surface). Then the PA-Cu2O coated PET fabric was dried at 160°C for 3 min to obtain the structural color photonic crystal fabric.
[0134] 10) Preparation of polydimethylsiloxane (PDMS) solution
[0135] The SYGARD184 silicone elastomer base produced by Dow Corning Corporation of the United States, the SYGARD184 silicone elastomer agent polydimethylsiloxane and the silane coupling agent (curing agent) are evenly mixed in a ratio of 10:1 (v / v) to obtain a polydimethylsiloxane (PDMS) solution.
[0136] 11) Preparation of washable structural color fabrics
[0137] The fabric prepared in step 9) is immersed in the polydimethylsiloxane (PDMS) solution prepared in step 10) (ensuring that the fabric is always immersed during the immersion process) for 10 minutes, and then dried (at 80° C. for 2 hours) to obtain a structural color fabric covered with a PDMS film. The fabric has good water-washing resistance.
[0138] The invention improves the water-washing resistance of the structural color fabric.
[0139] Experiment 1, fading:
[0140] The structural color fabrics obtained in all the above cases were tested according to the EU standard ISO105-X12:2001 "Color fastness to rubbing of textiles". The specific steps and test parameters are as follows: using a rubbing color fastness tester, wrapping a cylindrical friction finger with a diameter of (16±0.1) mm with dry or wet standard cotton cloth, and rubbing the fabric sample back and forth 10 times under a pressure of 9N. Then, a color fastness rating instrument was used to assess the dry / wet rubbing fastness grade of the fabric sample according to the degree of staining of the standard cotton, wherein the linear reciprocating stroke was (104±3) mm, and the fabric sample specification was 50mm×140mm. The results obtained are as follows: the dry / wet rubbing grades of the structural color fabrics prepared in Examples 1 to 5 are all 5 and 4, indicating that the friction resistance of the fabric has basically reached the standard for daily use.
[0141] Experiment 2, antibacterial:
[0142] The antibacterial properties of the structural color fabrics obtained in all the above cases were evaluated by the oscillation method according to GB / T20944.3-2008. Specifically, the structural color fabrics were cut into 5 cm × 5 cm squares, 0.75 g of the sample was mixed with 70 ml of 0.03 mol / L phosphate (PBS) buffer and a viable bacterial count of 1 × 10 9 CFU / mL~5×10 9 5 ml of bacterial suspension with CFU / mL was mixed. After 18 hours of contact and shaking, 1 ml of the above liquid was added to PBS of appropriate concentration. Gram-negative Escherichia coli (E.coli) and Gram-positive Staphylococcus aureus (S.Ureu) were selected as experimental strains. The antibacterial rate of the structural color fabric was obtained by the number of colonies in the culture dish.
[0143] The results obtained in Example 4 are as follows:
[0144] The antibacterial efficiency (antibacterial rate) of PET fabric treated with Cu2O structural color against Escherichia coli and Staphylococcus aureus were 100% and 99.62% respectively.
[0145] The results obtained in Example 1 are as follows:
[0146] The antibacterial efficiency (antibacterial rate) of black polyester fabric treated with Cu2O structural color against Escherichia coli and Staphylococcus aureus was 99.87% and 99.42% respectively.
[0147] Therefore, it is shown that Example 1 and Example 4 have good antibacterial properties against both Gram-positive bacteria (Staphylococcus aureus ATCC 25923) and Gram-negative bacteria (Escherichia coli ATCC 25922).
[0148] There is no significant difference in the antibacterial effect between Examples 2-1 to 2-4, Example 3 and Example 5 and Example 1.
[0149] Experiment 3: Washability
[0150] The washable structural color fabric obtained in Example 5 was tested according to GB / T 5713-2013. The specific experimental method is: the composite structural color fabric is combined with two cotton fabrics, immersed in water, squeezed to remove water, placed between two flat plates, and separated from the composite structural color fabric and cotton fabric after being subjected to a specified pressure. A gray sample card or a spectrophotometer is used to evaluate the discoloration of the sample and the staining of the adjacent fabric. The results obtained are: since the upper and lower surfaces of the composite structural color fabric are both PDMS with good hydrophobic properties, the sample does not change color, and the cotton fabric does not stain. The color of the fabric is not affected before and after the water treatment. Specifically, Figure 5 described.
[0151] Example 6: The "copper acetate monohydrate (C4H3CuO4·H2O)" in step 1) of Example 1 is replaced by any of the following: copper nitrate trihydrate, copper sulfate, copper chloride, and the molar amount remains unchanged, which is still 0.0017 mol; the rest is the same as Example 1.
[0152] The performance of the three products finally obtained was not significantly different from that of Example 1, and all of them had the characteristics of good antibacterial property and not easy to fade.
[0153] Comparative Example 1: The dropwise addition of step 4) and step 5) in Example 1 was changed to a one-time addition, and the rest was the same as Example 1.
[0154] The final Cu2O microspheres obtained by comparison with Example 1 show that the content of Cu2O microspheres obtained by adding once is only 1 / 4 to 1 / 3 of that obtained by adding dropwise, and the Cu2O microspheres obtained are of uneven size. This is because in the liquid phase reduction method, a soluble salt containing Cu2O is usually used as Cu2O. 2+ Copper source, after adding precipitant (alkaline substance) to form Cu(OH)2 or CuO precursor, then reduced to Cu with reducing agent + , after nucleation and growth, finally Cu2O single crystals of various morphologies are formed. Too fast addition of sodium hydroxide results in less precursor formation, insufficient subsequent reaction, and less product. Slowly add part of the reducing agent to ensure uniform formation of seeds through low-speed nucleation; in the second growth stage, quickly add the remaining reducing agent to ensure that Cu+ The one-time addition of ascorbic acid leads to uneven nucleation rate and uneven particle size.
[0155] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A method for preparing a Cu2O microsphere structured color fabric, characterized in that The following steps are involved: 1) Prepare copper source precursor solution: Add polyvinyl pyrrolidone, trisodium citrate dihydrate and dibasic copper salt in a molar ratio of 7.8:0.8-1.2:1-1.8 to a mixed solvent consisting of diol and deionized water, and disperse them uniformly to form a copper source precursor solution; 2) Prepare sodium hydroxide solution: Dissolve sodium hydroxide in ionized water to obtain a sodium hydroxide solution; 3) Prepare reducing agent solution: dissolving a reducing agent in deionized water to obtain a reducing agent solution; 4) Under vigorous stirring conditions, the sodium hydroxide solution prepared in step 2) is added to the copper source precursor solution prepared in step 1) in a molar ratio of sodium hydroxide to binary copper salt of 3 to 6:1, and after vigorous stirring, a solution 1 is obtained; 5) Under stirring conditions, the reducing agent solution obtained in step 3) is added to the solution 1 obtained in step 4) at a molar ratio of reducing agent: binary copper salt = 1.05-1.2:1, and dispersed evenly to obtain solution 2; 6) performing solid-liquid separation on the solution 2 obtained in step 5), washing and drying the separated solid to obtain Cu2O single crystal spheres; 7) Prepare Cu2O single crystal sphere dispersion: Cu2O single crystal spheres are dispersed in anhydrous ethanol to obtain a uniformly dispersed Cu2O single crystal sphere dispersion; In the Cu2O single crystal sphere dispersion liquid, the concentration of the Cu2O single crystal sphere dispersion is 1.% to 2.5wt%; 8) Preparation of binder dispersion: The binder is dispersed in deionized water to obtain a uniformly dispersed binder dispersion; In the binder dispersion, the concentration of the binder dispersion is 5% to 30wt%; 9) Firstly, the adhesive dispersion is sprayed on the surface of the fabric, and then the fabric is dried for the first time to obtain the pretreated fabric; Then, the Cu2O single crystal ball dispersion is sprayed on the surface of the pretreated fabric, and then secondary drying is performed to obtain the Cu2O microsphere structure color fabric.
2. The method for preparing a Cu2O microsphere structure color fabric according to claim 1, characterized in that: In step 1), the binary copper salt is any one of the following: copper acetate monohydrate, copper nitrate trihydrate, copper sulfate, copper chloride; In step 3), the reducing agent is any one of the following: ascorbic acid, hydroxylamine hydrochloride; The binder in step 8) is a resin binder.
3. The method for preparing a Cu2O microsphere structure color fabric according to claim 2, characterized in that: In step 1), the diol is any one of the following: butanediol, pentanediol, ethylene glycol, hexanediol, diethylene glycol; In step 8), the resin binder is any one of the following: polyacrylates, polyvinyl alcohol.
4. The method for preparing a Cu2O microsphere structure colored fabric according to any one of claims 1 to 3, characterized in that: In the step 1), the ratio of the binary copper salt to the mixed solvent is 0.0017 mol to 0.0051 mol / 130 ml to 260 ml; in the mixed solvent, the volume ratio of the diol to deionized water is 2 to 4:10; In the step 2), the concentration of the sodium hydroxide solution is 0.3 to 1.0 M; In the step 3), the concentration of the reducing agent solution is 0.1M to 1.0M.
5. The method for preparing a Cu2O microsphere structure colored fabric according to any one of claims 1 to 4, characterized in that: Steps 1) to 8) are all carried out at a temperature of 5 to 50° C.; The rate of vigorous stirring in step 4) is 1000-1200 r / min, and the remaining stirring rates are 300-900 r / min; In the step 1), the stirring time is 20 min to 3 h; the ultrasonic dispersion time is 5 to 60 min; In step 4), the sodium hydroxide aqueous solution is added to the copper source precursor solution by dropwise addition for 10 to 20 minutes; the vigorous stirring time is 5 to 60 minutes; In step 5), the reducing agent solution is added to solution 1 by dripping twice, each dripping time is 18 to 38 seconds; the interval time between two dripping is 5 to 30 minutes; after the dripping is completed, stirring is performed for 60 to 80 minutes, and ultrasonic dispersion is performed for 5 to 60 minutes; stirring is still maintained during the interval time between two dripping; In step 6), a centrifuge is used to separate solid and liquid, and the centrifugation is performed at a speed of 4000 to 12000 r / min for 5 to 30 min; The stirring time of step 7) is 5 to 30 minutes; The stirring time of step 8) is 5 to 30 minutes.
6. A method for preparing a Cu2O microsphere structure colored fabric according to any one of claims 1 to 5, characterized in that: The step 9) is: spraying is performed by a spray gun connected to an air compressor, the pressure applied by the air compressor is 0.5 PSI, and the diameter of the spray gun is 0.2 mm.
7. A method for preparing a Cu2O microsphere structure colored fabric according to any one of claims 1 to 6, characterized in that: In the step 6): The washing is performed using a mixed solution of water and ethanol; in the mixed solution, the volume ratio of water to ethanol is 1:1; The drying step is: drying in a vacuum oven at 50±10°C for 3±0.5h; In the step 9): The first drying is to place it in a 100±10℃ air drying oven for 1±0.1min; The secondary drying is to first place it in a forced air drying oven at 160±10℃ and dry it for 3±0.3min.
Citation Information
Patent Citations
Monodisperse Cu2O single crystal solid sphere with controllable particle size and preparation method thereof
CN109850932A
Fabric with high-brightness and high-stability structural color and preparation method thereof
CN113957729A
Cited By
A color-mixed structural color fabric and a preparation method thereof
CN120384422B